Eco-systemic transitions: A holistic vision of international students’ transition experiences to British higher education - Berrouaine, Imene (2022)
Students’ academic transitions have attracted considerable attention as a widely theorised and a thoroughly researched multi-faceted topic. Prime discourses have sparked some of the most prominent and controversial debates about the theoretical underpinnings of ‘students’ transition’ into higher education’ and its implications for praxis. In the British higher education (HE) landscape, the university is subjected to conflicting pressures – between expectations, demands, and retentions – in the light of increased diversity in the student body. Student voice and engagement acted as a vehicle of empowerment in (re) shaping educational policies.